The effects of the COVID-19 pandemic on breast cancer diagnosis and treatment, a systematic review of the literature (Research, Society and Development, 2023)
Introduction: Breast cancer ranks second in terms of the highest incidence among females, second only to non-melanoma skin cancer. The advent of the COVID-19 pandemic generated a fruitless scenario for early diagnosis and treatment, directly impacting the survival and prognosis of these patients. Measuring the extent of such an impact is vital to devise a countermeasure aimed at repairing such diagnoses. Thus, the current study proposes to carry out a systematic review of the literature on the impacts of COVID-19 on the screening and treatment of breast cancer in Brazil. Methodology: The literature was searched, through the SCIELO, LILACS and MEDLINE platforms, using the descriptors Breast cancer, COVID-19 associated with the Boolean operator AND, original articles resulting from quantitative and/or qualitative analyzes directly about the difficulties imposed by the COVID-19 pandemic. 19 to screening and coping with breast cancer in Brazil. Results: 35 articles were found, of which 10 were included in the analysis. Conclusion: Due to the pandemic, there was a significant drop in the number of mammograms, a reduction in early-stage cancer diagnoses, an increase in symptomatic cancer cases and an increase in chemotherapy costs for advanced diseases.